Low-viscosity UHPC decorative plate and preparation method thereof

By using the method of layered mesh cloth and layered roll forming in the UHPC decorative panel, the problems of high viscosity, poor fluidity and poor fiber stirring uniformity are solved, and the high strength, low viscosity and stable surface effect of the material is achieved.

CN119874275AInactive Publication Date: 2025-04-25DAOZHEN (BEIJING) TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411357481.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Due to the high viscosity and poor fluidity of UHPC decorative panels, the jet processing is difficult, the surface effect is unstable, and the fiber stirring uniformity is poor, affecting the material performance.

Method used

The method of adding a grid cloth in layers is used to improve the bending and tensile strength of UHPC structural plates, reduce the use of organic fibers, and increase density and flatness through layered roll molding to ensure the stability of the surface effect.

Benefits of technology

It effectively improves the bending and tensile strength of UHPC structural plates, reduces the difficulty of stirring, significantly improves the density and flatness of the material, and ensures the stability of the surface effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874275A_ABST
    Figure CN119874275A_ABST
Patent Text Reader

Abstract

The invention provides a low-viscosity UHPC decorative plate and a preparation method thereof, and relates to the technical field of rare earth hexaboride cathode materials. Comprising a structural layer and a surface layer, the structural layer is prepared from the following materials in percentage by weight: 30 to 40 weight percent of white cement, 5 to 10 weight percent of special white silica powder, 5 to 10 weight percent of microbeads, 40 to 45 weight percent of textured quartz sand, 0.2 to 0.5 weight percent of efficient water reducing agent, 0.02 to 0.5 weight percent of defoaming agent, 0.1 to 0.4 weight percent of organic fiber, and the balance of water, and n layers of gridding cloth. In addition, due to the addition of the gridding cloth, the addition of organic fibers can be reduced, and the stirring difficulty is reduced; the density and flatness of the UHPC structural plate can be remarkably improved in a layered rolling forming mode, and then the surface effect is stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rare earth hexaboride cathode materials, and in particular relates to a low-viscosity UHPC decorative board and a preparation method thereof. Background Art

[0002] UHPC has ultra-high strength, ultra-low water absorption, super durability and corrosion resistance. The compressive strength of UHPC currently used in the construction application field is greater than 160 MPa, and the flexural strength is greater than 20 MPa. Although UHPC can achieve very high compressive strength, fiber building components mainly use the flexural strength of UHPC. In practical applications, the ultra-high strength of the UHPC matrix is ​​further enhanced and toughened by adding alkali-resistant glass fiber, polyvinyl alcohol fiber, and steel fiber in different proportions.

[0003] The base materials of UHPC are not unfamiliar to those who are familiar with the concrete industry: water, sand, cement, silica fume, admixtures. It sounds simple, but UHPC is a different grade compared to ordinary concrete. There is no secret ingredient: resin, cellulose or special polymers are not used. The secret lies in the ultra-fine particles and carefully selected particle chemical properties, and these particles are properly mixed, poured and cured to achieve a close packing of the matrix and strong molecular bonding.

[0004] At present, in order to achieve the surface effect of UHPC decorative panels, the surface of UHPC decorative panels is generally treated by spraying process. However, the main characteristics of ultra-high performance concrete are large amount of gel material, high amount of silica fume, and extremely low water-cement ratio, which leads to high viscosity and reduced fluidity, which in turn leads to high difficulty in spraying processing and unguaranteed surface effect; at present, UHPC prefabricated decorative panels are mainly cast, but the cost of casting process to produce special-shaped structure molds is very high, the surface effect cannot be guaranteed, and the specifications of embedded parts are limited. In addition, a large amount of fiber needs to be added to UHPC, but it is difficult to completely mix the fiber evenly by ordinary mixing process. Therefore, those skilled in the art provide a low-viscosity UHPC decorative panel and its preparation method to solve the above-mentioned technical problems. Summary of the invention

[0005] Technical issues

[0006] In order to solve the technical problem, the present invention adopts the following technical scheme: the UHPC decorative board includes a structural layer and a surface layer; the structural layer manufacturing materials include: 30-40wt.% white cement; 5-10wt.% special white silica powder; 5-10wt.% microbeads; 40-45wt.% textured quartz sand; 0.2-0.5wt.% high-efficiency water reducing agent; 0.02-0.5wt.% defoaming agent; 0.1-0.4wt.% organic fiber; the rest is water, and n layers of mesh cloth;

[0007] Preferably, the surface layer manufacturing materials include: 30-40wt.% white cement; 5-10wt.% special white silica powder; 5-10wt.% micro beads; 40-45wt.% textured quartz sand; 0.1-0.5wt.% high-efficiency water reducing agent; 0.02-0.5wt.% defoaming agent; 0.2-0.6wt.% acrylic emulsion; 0.1-0.4wt.% organic fiber; and the rest is water:

[0008] Preferably, the materials for making the structural layer include: 800kg of cement, 200kg of special white silica powder, 200kg of microbeads, 1100kg of textured quartz sand, 10kg of high-efficiency water reducing agent, 1kg of defoaming agent, 5kg of organic fiber, and 155kg of water.

[0009] Preferably, the surface layer making materials include: 800kg cement, 200kg special white silica powder, 200kg microbeads, 1100kg textured quartz sand, 3kg high-efficiency water reducing agent, 0.8kg defoaming agent, 10kg polypropylene emulsion, 190kg water, and 112kg organic fiber.

[0010] Preferably, the specially prepared white silicon powder is silicon powder that has been screened through high temperature calcination and has a particle size of 0.1-10 μm.

[0011] Preferably, the particle size of the microbeads is 30-60 μm.

[0012] Preferably, the method comprises the following preparation steps:

[0013] After measuring the UHPC decorative board structural layer material, quantitatively release it into the mixer, wherein there is at least one mixer, and a plurality of mixers are arranged in sequence along the conveyor belt;

[0014] The structural layer template is coated with a release agent;

[0015] The first mixer stirs the materials of each structural layer, and spreads the uniformly mixed structural layer materials on the structural layer template to obtain a layer of material plate;

[0016] Laying a first layer of mesh cloth on the first layer of material board to obtain a layer of mesh cloth board;

[0017] The layer of mesh cloth plate is roll-formed by a forming pair of rollers to obtain a first UHPC structural plate, wherein the thickness of the first UHPC structural plate is 5-10 mm;

[0018] The second mixer spreads the structural layer material onto the first UHPC structural board to obtain a second layer material board;

[0019] Laying a second layer of mesh cloth on the second layer of material board to obtain a second layer of mesh cloth board;

[0020] Preferably, the second layer of mesh cloth plate is roll-formed by forming rollers to obtain a second UHPC structural plate, and the thickness of the second UHPC structural plate is 10-20 mm;

[0021] Preferably, the second UHPC structural panel moves forward along the conveyor belt to finally obtain a UHPC structural panel, wherein the UHPC structural panel comprises n layers of mesh cloth.

[0022] Preferably, the UHPC decorative board includes a UHPC embedded component decorative board and a UHPC non-embedded component decorative board, and the UHPC decorative board manufacturing method further includes:

[0023] The surface material of the UHPC decorative board is measured and quantitatively released into the surface mixer;

[0024] The surface layer template is coated with a release agent;

[0025] When manufacturing the UHPC embedded component decorative board, the UHPC structural board is laid on the surface layer in two layers, and embedded components are placed between the two layers of the UHPC structural board to obtain the UHPC embedded component decorative board.

[0026] Preferably, when manufacturing the UHPC decorative panel without embedded parts, the manufacturing method comprises: laying the UHPC structural panel on the surface layer to obtain the UHPC decorative panel without embedded parts.

[0027] Preferably, the second UHPC structural panel moves forward along the conveyor belt to finally obtain a UHPC structural panel, comprising:

[0028] The second UHPC structural panel moves forward along the conveyor belt to obtain an nth UHPC structural panel;

[0029] The nth UHPC structural panel is cut, cured, demoulded and surface treated to finally obtain a UHPC structural panel.

[0030] Preferably, in some embodiments of the present invention, n is 1, 2, 3, 4, or 5.

[0031] In some embodiments of the present invention, n is 2, 3, 4 or 5.

[0032] In some embodiments of the present invention, the second UHPC structural panel moves forward along the conveyor belt to finally obtain a UHPC structural panel, including:

[0033] The second UHPC structural panel moves forward along the conveyor belt to obtain an nth UHPC structural panel;

[0034] The nth UHPC structural panel is cut, cured, demoulded and surface treated to finally obtain a UHPC structural panel.

[0035] Beneficial effects:

[0036] Compared with the prior art, the beneficial effects are as follows:

[0037] The present invention can effectively increase the bending and tensile strength of the UHPC structural plate by adding mesh cloth in layers. In addition, the addition of mesh cloth can also reduce the addition of organic fibers, reducing the difficulty of stirring; the density and flatness of the UHPC structural plate can be significantly improved by layered roll forming, thereby stabilizing the surface effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a flow chart of the method for making the UHPC decorative board of the present invention;

[0039] Figure 2 Schematic diagram of the formula of the UHPC decorative board of the present invention;

[0040] Figure 3 Schematic diagram of the formula of the surface layer of the UHPC decorative board of the present invention. DETAILED DESCRIPTION

[0041] The present invention is described below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. Any modification and improvement made without changing the inventive concept belongs to the protection scope of the present invention.

[0042] Specifically, the materials for making the structural layer include: 30-40wt.% white cement; 5-10wt.% special white silica powder, 5-10wt.% microbeads, 40-45wt.% textured quartz sand, 0.2-0.5wt.% high-efficiency water reducing agent, 0.02-0.5wt.% defoaming agent, 0.1-0.4wt.% organic fiber, and the rest is water, and there are n layers of mesh cloth, where n can be 1, 2, 3, 4, or 5; the materials for making the surface layer include: 30-40wt.% white cement; 5-10wt.% special white silica powder, 5-10wt.% microbeads, 40-45wt.% textured quartz sand, 0.1-0.5wt.% high-efficiency water reducing agent, 0.02-0.5wt.% defoaming agent, 0.2-0.6wt.% acrylic emulsion, 0.1-0.4wt.% organic fiber, and the rest is water.

[0043] Among them, the special white silicon micropowder is silicon micropowder that has been screened by high-temperature calcination. The high-temperature calcination reduces the closure of microcracks generated during ball milling on the surface of the silicon micropowder, and the edges and corners are rounded. The particle size of the special white silicon micropowder can be 0.1-10μm. Preferably, the particle size of the special white silicon micropowder can be 2μm, D50. Particles of this particle size can fill the gaps between cement and microbead particles, reducing water consumption. The addition of special white silicon micropowder makes it easier for the raw material particles to slide relative to each other, and can also ensure a faster flow rate and a larger expansion degree under low water-cement ratios. The particles do not have edges and corners, and are less likely to generate bubbles during stirring. The large bubbles generated can be discharged to the surface in a short time, increasing the density of the product material structure system, thereby increasing its strength; in addition, microbeads can also replace cement, reduce hydration heat, and increase dimensional stability.

[0044] The addition of microbeads can block the flocculation structure that cement quickly forms and prolong the time for surface crusting. Generally, UHPC will lose water and form a hard crust when exposed to air for about 10 minutes above 25°C. The crusting time is extended to 30 minutes after the addition of microbeads. In addition, the spherical shape of microbeads can make it easier for particles to slide relative to each other, and can also ensure a faster flow rate and a larger expansion degree under low water-cement ratio. The particles do not have edges and corners, and it is less likely to generate bubbles during stirring. The large bubbles generated can be discharged to the surface in a short time, which increases the density of the product material structure system and thus increases its strength. In addition, microbeads can also replace cement, reduce hydration heat, and increase dimensional stability. In some embodiments of the present invention, the particle size of the microbeads can be 30-60μm, and preferably, the particle size of the microbeads can be 45μm.

[0045] The spherical shape of textured quartz sand can make it easier for the particles to slide relative to each other. The addition of textured quartz sand can ensure a faster flow rate and a larger expansion degree under the condition of low water-cement ratio. The particles have no edges and corners, which makes it less likely to generate bubbles during the mixing process. The large bubbles generated can be discharged to the surface in a short time, which increases the density of the product material structure system and thus increases its strength. In some embodiments of the present invention, textured quartz sand includes two particle sizes, and the two particle sizes of textured quartz sand are 20-40 mesh and 40-80 mesh, respectively. The mass ratio of 20-40 mesh textured quartz sand and 40-80 mesh textured quartz sand is 1:1. After the most compact stacking test, it is determined that the same mass volume has the smallest density when textured quartz sand of different particle sizes is mixed in a 1:1 ratio.

[0046] The high-efficiency water reducer can be a polycarboxylic acid liquid water reducer, and the concentration can be 45%. The high-efficiency water reducer has a high water reduction rate. The high-efficiency water reducer is selected from the water reducer that is prone to bleeding and bottoming in ordinary concrete. In UHPC, it can reduce the thickness of the water film wrapped around the particles, reduce the water consumption, improve the density of the slurry, and increase the strength. The defoamer can be a modified silicone defoamer. The defoamer can effectively reduce the formation of bubbles during stirring, especially the bubbles with larger diameters burst to form beneficial bubbles with a diameter of less than 10μm. The bubbles are more likely to be discharged to the surface and burst, bringing out a small amount of water, slowing down the surface skinning time. Low viscosity is achieved by rationally optimizing the material and coordinating with the water reducer and defoamer.

[0047] Organic fibers include polypropylene fibers, polyacrylonitrile fibers, polyoxymethylene fibers, and polyvinyl alcohol fibers. The addition of organic fibers is mainly to prevent the generation of microcracks and prevent the structural layer from bursting at high temperatures (above 600°C). In some embodiments of the present invention, the diameter of the organic fiber can be 45μm-0.18mm and the length can be 6mm-15mm. The selection of organic fibers is determined based on the thickness of the structural layer cast in a single casting and the decorative effect. Selecting fibers with a diameter of 0.1mm and a length of 6mm can make their crack resistance and explosion-proof performance meet the high temperature 3h requirements, and the material fluidity is not affected.

[0048] There are n layers of mesh cloth, where n can be 1, 2, 3, 4, or 5. Preferably, 5 layers of mesh cloth are laid. Laying 5 layers of mesh cloth is equivalent to a fiber content of 15%. 5 layers of mesh cloth are easier to approach the surface during construction and can better play a toughening role. In some embodiments of the present invention, the mesh diameter of the mesh cloth is 8mm, and the national standard 130g mesh cloth is 10mm. If the mesh diameter of the mesh cloth is too large, the crack spacing will increase when it is subjected to force, and the flexural strength of the same quality and the same number of layers will be reduced by 10%. If the mesh diameter is too small, it will be difficult for large particles in UHPC to pass through, and stratified failure will occur when it is damaged.

[0049] In some embodiments of the present invention, 0-3% of the total mass of the surface layer by weight of iron oxide color powder and 0-50% of coarse aggregate may be added to the surface layer according to the decoration requirements.

[0050] In some embodiments of the present invention, the materials for making the structural layer include: 800kg of cement, 200kg of special white silica powder, 200kg of microbeads, 1100kg of textured quartz sand, 10kg of high-efficiency water reducing agent, 1kg of defoaming agent, 5kg of organic fiber, and 155kg of water.

[0051] In some embodiments of the present invention, the surface layer making materials include: 800kg of cement, 200kg of special white silica powder, 200kg of microbeads, 1100kg of textured quartz sand, 3kg of high-efficiency water reducing agent, 0.8kg of defoaming agent, 10kg of polypropylene emulsion, 190kg of water, and 5kg of organic fiber.

[0052] like Figure 1 As shown, the present invention provides a method for manufacturing a UHPC decorative board, comprising the following steps:

[0053] S1. After measuring the UHPC decorative board structural layer materials, quantitatively release them into the mixer. There is at least one mixer, and multiple mixers are arranged in sequence along the conveyor belt.

[0054] The screw conveyor transports the UHPC decorative board structural layer material to the weighing scale for measurement, and then releases the quantitative material into the mixer. There is at least one mixer, and multiple mixers are arranged in sequence along the conveyor belt. Multiple mixers are to meet the needs of multiple feeding. In addition, in order to facilitate the distinction of description, the multiple mixers are named the first mixer, the second mixer, and the third mixer respectively;

[0055] S2, coating the release agent on the structural layer template;

[0056] The plate loading machine absorbs the structural layer template and conveys it to the oil coating machine, and the oil coating machine coats the mold release agent on the structural layer template. Furthermore, in some embodiments of the present application, when the structural layer template coated with the mold release agent is a structural layer flat template, the structural layer flat template moves forward through the conveyor belt and enters the forming unit. It should be noted that when the structural layer template is a structural layer special-shaped template, it does not enter the assembly line forming unit, and is manually roll-formed during the roll-forming step, and does not need to enter the forming unit;

[0057] S3, the first mixer stirs the materials of each structural layer, and the uniformly mixed structural layer materials are spread on the structural layer template to obtain a layer of material plate;

[0058] The first mixer stirs the materials of each structural layer, and releases the uniformly mixed structural layer materials into the hopper of the molding machine. By opening the hopper valve, the structural layer materials are released into the molding unit. In the molding unit, the structural layer materials are spread on the structural layer template to obtain a layer of material board;

[0059] S4, laying a first layer of mesh cloth on a layer of material board to obtain a layer of mesh cloth board;

[0060] Lay the first layer of mesh cloth on a layer of material board to obtain a layer of mesh cloth board. Among them, the first layer of mesh cloth includes glass fiber surface felt, glass fiber mesh cloth, basalt fiber mesh cloth, polypropylene fiber mesh cloth, and nylon fiber mesh cloth. The mesh diameter of the first layer of mesh cloth is 5mm, and the national standard 80g mesh cloth is 10mm. If the mesh of the mesh cloth is too large, the crack spacing will increase when it is stressed, and the flexural strength of the same quality and the same number of layers will be reduced by 10%. If the mesh is too small, it is difficult for large particles in UHPC to pass through, and stratified failure will occur when it is damaged;

[0061] S5, a layer of mesh cloth plate is roll-formed by a forming pair of rollers to obtain a first UHPC structural plate, the thickness of the first UHPC structural plate is 5-10 mm;

[0062] The roll forming here can be performed on the assembly line in the forming unit, or can be performed manually. Specifically, when a layer of mesh cloth board is a flat plate, it can be roll formed on the assembly line in the forming unit, and when a layer of mesh cloth board is a special-shaped board, it can be manually roll formed;

[0063] S6, the second mixer spreads the structural layer material onto the first UHPC structural plate to obtain a second layer material plate;

[0064] The first UHPC structural board continues to be transported forward, and when it reaches the second mixer, the structural layer material in the second mixer is spread onto the first UHPC structural board to obtain a second layer material board;

[0065] S7, laying a second layer of mesh cloth on the second layer of material board to obtain a second layer of mesh cloth board;

[0066] Step S7: laying the mesh cloth is the same as step S4;

[0067] S8, the second layer of mesh cloth plate is roll-formed by a forming roller to obtain a second UHPC structural plate, and the thickness of the second UHPC structural plate is 10-20 mm;

[0068] The second layer of mesh cloth plate is roll-formed by a forming pair of rollers to obtain a second UHPC structural plate, and the thickness of the second UHPC structural plate is 10-20 mm, that is, the thickness of the second UHPC structural plate is 5-10 mm thicker than that of the first UHPC structural plate. Similar to step S5, the roll forming here can also be performed on the assembly line in the forming unit, or can be manually roll-formed;

[0069] S9, the second UHPC structural plate moves forward along the conveyor belt, and finally a UHPC structural plate is obtained, wherein the UHPC structural plate includes n layers of mesh cloth;

[0070] The second UHPC structural panel moves forward along the conveyor belt, and the structural layer materials are spread on the structural panel in layers, and then a mesh cloth is laid, and then the panel is roll-formed by a forming roller to finally obtain a UHPC structural panel, which includes n layers of mesh cloth. Among them, n can be 1, 2, 3, 4, or 5. In some embodiments of the application, the second UHPC structural panel moves forward along the conveyor belt to finally obtain a UHPC structural panel, including: the second UHPC structural panel moves forward along the conveyor belt to obtain the nth UHPC structural panel; the third UHPC structural panel, the fourth UHPC structural panel, and the fifth UHPC structural panel can be obtained in the same manner as the steps for obtaining the first UHPC structural panel and the second UHPC structural panel. The nth UHPC structural panel is cut, cured, demolded, and surface treated to finally obtain a UHPC structural panel. The UHPC structural panel does not contain a decorative surface, and the surface decoration effect is fixed as a low-cost product;

[0071] S10, measuring and quantitatively releasing the surface material of the UHPC decorative board into the surface mixer;

[0072] S11, the surface layer template is coated with a release agent, and the surface layer template includes a surface layer flat template and a surface layer special-shaped template;

[0073] S12, releasing the surface layer material in the surface layer mixer onto the surface of the surface layer template to obtain the surface layer, the surface layer material in the surface layer mixer is released onto the surface of the surface layer template, including spraying the surface layer material in the surface layer mixer onto the surface of the surface layer template by a spray gun, or pouring the surface layer material in the surface layer mixer onto the surface of the surface layer template, the UHPC decorative board includes a UHPC embedded decorative board and a UHPC decorative board without embedded parts, and the methods for making the UHPC embedded decorative board and the UHPC decorative board without embedded parts are different, such as step S13 and step S14;

[0074] S13. When making UHPC embedded decorative panels, the UHPC structural panels are laid on the surface layer twice, and embedded parts are placed between two layers of UHPC structural panels to obtain UHPC embedded decorative panels. After a single UHPC structural panel is formed (it can be single-layer or multi-layer), the UHPC structural layer material is coated about 2-3mm between the two UHPC structural panels, and embedded parts are placed between the two layers of UHPC structural panels. After the two layers are laid, they are compacted with a roller to obtain UHPC embedded decorative panels. The embedded parts are used to fix them to the exterior wall or install the back keel in the future, in order to facilitate the later installation. In addition, since the UHPC structural panels need to be laid on the surface layer evenly and forcefully twice at this time, at least 2 layers of UHPC structural panels are required. Therefore, when making UHPC embedded decorative panels, n is 2, 3, 4, and 5. The structural layer is laid twice, but the thickness of each layer and the number of times the mesh is laid can be adjusted. It should be noted that the surface layer can be placed directly after the UHPC structural layer is formed, or before forming;

[0075] S14. When manufacturing the UHPC decorative board without embedded parts, the UHPC structural board is laid on the surface layer and rolled to be compacted to obtain the UHPC decorative board without embedded parts.

[0076] It should be noted that when a UHPC decorative flat plate is made using a flat surface template, the "rolling and compacting" step in step S13 and step S14 is performed by automatic rolling using a pressure roller on a molding production line. However, when a UHPC decorative special-shaped plate is made using a special-shaped surface template, the "rolling and compacting" step in step S13 and step S14 is performed by manual rolling using a pressure roller.

[0077] 1. Experimental purpose: To compare the effects of different microsilica powder on the performance of UHPC decorative panels

[0078] 2. Test operation:

[0079] a. Structural layer production

[0080] White cement, special white silica powder or white silica powder with different particle sizes, textured quartz sand, water, high-efficiency water reducing agent and defoaming agent are mixed and stirred according to proportion to obtain a mixed slurry.

[0081] b. Surface preparation

[0082] White cement, special white silica powder or white silica powder with different particle sizes, textured quartz sand, water, high-efficiency water reducing agent and defoaming agent are mixed and stirred according to proportion to obtain a mixed slurry.

[0083] The above experimental operations are all the same except for the different types of white silica powder used.

[0084] 3. Performance test:

[0085] Table 1 Comparison of different white silicon powders

[0086]

[0087]

[0088] It should be noted that both the fluidity test and the compressive strength test are conducted on the mixed slurry produced before the assembly line is formed, so the test operation part does not involve the production of the board. In addition, the fluidity is measured according to the fluidity of the mortar, and the jumping table does not jump; the compressive strength test is also based on the mortar strength test standard.

[0089] It can be seen from Table 1 that the UHPC decorative board obtained when using the special white silica powder has the performance characteristics of good fluidity and high strength.

[0090] Example 2

[0091] 1. Experimental purpose: To compare the effects of different dosages of special white silica powder on the performance of UHPC decorative panels

[0092] 2. Test operation:

[0093] a. Structural layer production

[0094] White cement, special white silica powder, textured quartz sand, water, high-efficiency water reducing agent and defoaming agent are mixed and stirred according to proportion to obtain a mixed slurry.

[0095] b. Surface preparation

[0096] White cement, special white silica powder, textured quartz sand, water, high-efficiency water reducing agent and defoaming agent are mixed and stirred according to proportion to obtain a mixed slurry.

[0097] Except for the different dosage of special white silica powder, the other experimental operations are all the same.

[0098] 3. Performance test:

[0099] Table 2 Comparison of different white silicon powder dosages

[0100]

[0101] It should be noted that both the fluidity test and the compressive strength test are conducted on the mixed slurry produced before the assembly line is formed, so the test operation part does not involve the production of the board. In addition, the fluidity is measured according to the fluidity of the mortar, and the jumping table does not jump; the compressive strength test is also based on the mortar strength test standard.

[0102] It can be seen from Table 2 that the UHPC decorative board obtained when the white silica powder dosage is 200kg has high strength and good fluidity.

[0103] Example 3

[0104] 1. Experimental purpose: To compare the effects of different microsphere dosages on the performance of UHPC decorative panels

[0105] 2. Test operation:

[0106] a. Structural layer production

[0107] White cement, special white silica powder, microbeads or first-grade fly ash, textured quartz sand, water, high-efficiency water reducing agent and defoaming agent are mixed and stirred according to proportion to obtain a mixed slurry.

[0108] b. Surface preparation

[0109] White cement, special white silica powder, microbeads or first-grade fly ash, textured quartz sand, water, high-efficiency water reducing agent and defoaming agent are mixed and stirred according to proportion to obtain a mixed slurry.

[0110] The above experimental operations are all the same except for the different dosage of microbeads or primary fly ash.

[0111] 3. Performance test:

[0112] Table 3 Comparison of different microbead dosages

[0113]

[0114] It should be noted that both the fluidity test and the compressive strength test are conducted on the mixed slurry produced before the assembly line is formed, so the test operation part does not involve the production of the board. In addition, the fluidity is measured according to the fluidity of the mortar, and the jumping table does not jump; the compressive strength test is also based on the mortar strength test standard.

[0115] It can be seen from Table 3 that the UHPC decorative board obtained when the microbead content is 200kg has high strength and good fluidity, and when the same content of 200kg of primary fly ash is used, the strength and fluidity of the UHPC decorative board are obviously inferior to the effect of microbeads.

[0116] Example 4

[0117] 1. Experimental purpose: To compare the effects of different mesh cloth laying layers on the performance of UHPC decorative panels

[0118] 2. Test operation:

[0119] a. Structural layer production

[0120] White cement, special white silica powder, microbeads, textured quartz sand, water, high-efficiency water reducing agent and defoaming agent are mixed and stirred according to the proportion; introduced into the molding machine, spread the mesh cloth, and molded to obtain the structural layer.

[0121] b. Surface preparation

[0122] White cement, special white silica powder, microbeads, textured quartz sand, water, high-efficiency water reducing agent and defoaming agent are mixed and stirred according to proportion to obtain a surface layer.

[0123] c. UHPC decorative board production

[0124] Spray or pour the surface layer on the surface of the finalized mold; evenly lay the structural layer on the surface layer of the finalized mold and put in the embedded parts; fix the back plate and perform maintenance and demoulding.

[0125] The above experimental operations are all the same except for the different number of mesh cloth layers.

[0126] 3. Performance test:

[0127] Table 4 Comparison of mesh layers

[0128]

[0129]

[0130] It can be seen from Table 4 that the flexural strength of the UHPC decorative board obtained when the number of mesh cloth layers is 5 is the largest.

[0131] Example 5

[0132] 1. Experimental purpose: To compare the effects of different mesh holes on the performance of UHPC decorative panels

[0133] 2. Test operation:

[0134] a. Structural layer production

[0135] White cement, special white silica powder, microbeads, textured quartz sand, water, high-efficiency water reducing agent and defoaming agent are mixed and stirred according to the proportion; introduced into the molding machine, spread the mesh cloth, and molded to obtain the structural layer.

[0136] b. Surface preparation

[0137] White cement, special white silica powder, microbeads, textured quartz sand, water, high-efficiency water reducing agent and defoaming agent are mixed and stirred according to proportion to obtain a surface layer.

[0138] c. UHPC decorative board production

[0139] Spray or pour the surface layer on the surface of the finalized mold; evenly lay the structural layer on the surface layer of the finalized mold and put in the embedded parts; fix the back plate and perform maintenance and demoulding.

[0140] The above experimental operations are all the same except for the use of different mesh holes.

[0141] 3. Performance test:

[0142] Table 5 Comparison of holes of different mesh fabrics

[0143]

[0144] It can be seen from Table 5 that when the mesh size is 8 mm, the crack spacing of the UHPC decorative board is the smallest and the bending strength is the largest.

[0145] Example 6

[0146] 1. Experimental purpose: To compare the effects of different organic fiber dosages on the performance of UHPC decorative panels

[0147] 2. Test operation:

[0148] a. Structural layer production

[0149] White cement, special white silica powder, microbeads, textured quartz sand, organic fiber content, water, high-efficiency water reducing agent and defoaming agent are mixed and stirred according to the proportion; introduced into the molding machine, spread the mesh cloth, and molded to obtain the structural layer.

[0150] b. Surface preparation

[0151] White cement, special white silica powder, microbeads, textured quartz sand, water, high-efficiency water reducing agent and defoaming agent are mixed and stirred according to proportion to obtain a surface layer.

[0152] c. UHPC decorative board production

[0153] Spray or pour the surface layer on the surface of the finalized mold; evenly lay the structural layer on the surface layer of the finalized mold and put in the embedded parts; fix the back plate and perform maintenance and demoulding.

[0154] Except for the different organic fiber dosage, the other experimental operations are all the same.

[0155] 3. Performance test:

[0156] Table 6 Comparison of different organic fiber content

[0157]

[0158] It can be seen from Table 6 that the UHPC decorative board obtained when the organic fiber content is 5 kg is the most cost-effective and can also play a role in combustion and explosion resistance.

[0159] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A low-viscosity UHPC decorative board, characterized in that: UHPC decorative panels include a structural layer and a surface layer; The structural layer manufacturing materials include: 30-40wt.% white cement; 5-10wt.% special white silica powder; 5-10wt.% micro beads; 40-45wt.% textured quartz sand; 0.2-0.5wt.% high-efficiency water reducing agent; 0.02-0.5wt.% defoaming agent; 0.1-0.4wt.% organic fiber; the rest is water, and n layers of mesh cloth; The surface layer manufacturing materials include: 30-40wt.% white cement; 5-10wt.% special white silica powder, 5-10wt.% micro beads, 40-45wt.% textured quartz sand, 0.1-0.5wt.% high-efficiency water reducing agent, 0.02-0.5wt.% defoaming agent, 0.2-0.6wt.% acrylic emulsion, 0.1-0.4wt.% organic fiber, and the rest is water.

2. The low-viscosity UHPC decorative board according to claim 1, characterized in that: The materials for making the structural layer include: 800kg of cement, 200kg of special white silica powder, 200kg of microbeads, 1100kg of textured quartz sand, 10kg of high-efficiency water reducing agent, 1kg of defoaming agent, 5kg of organic fiber, and 155kg of water.

3. The low viscosity UHPC decorative board according to claim 1, characterized in that: The surface layer production materials include: 800kg cement, 200kg special white silica powder, 200kg microbeads, 1100kg textured quartz sand, 3kg high-efficiency water reducing agent, 0.8kg defoaming agent, 10kg polypropylene emulsion, 190kg water, and 112kg organic fiber.

4. The low-viscosity UHPC decorative board according to claim 1, characterized in that: The specially made white silicon micropowder is silicon micropowder that has been screened through high temperature burning, and has a particle size of 0.1-10 μm.

5. The low-viscosity UHPC decorative board according to claim 1, characterized in that: The particle size of the microbeads is 30-60 μm.

6. A method for preparing a low-viscosity UHPC decorative board, characterized in that: The use of the low-viscosity UHPC decorative board as described in claims 1 to 5 above includes the following preparation steps: After measuring the UHPC decorative board structural layer material, quantitatively release it into the mixer, wherein there is at least one mixer, and a plurality of mixers are arranged in sequence along the conveyor belt; The structural layer template is coated with a release agent; The first mixer stirs the materials of each structural layer, and spreads the uniformly mixed structural layer materials on the structural layer template to obtain a layer of material plate; Laying a first layer of mesh cloth on the first layer of material board to obtain a layer of mesh cloth board; The layer of mesh cloth plate is roll-formed by a forming pair of rollers to obtain a first UHPC structural plate, wherein the thickness of the first UHPC structural plate is 5-10 mm; The second mixer spreads the structural layer material onto the first UHPC structural board to obtain a second layer material board; Laying a second layer of mesh cloth on the second layer of material board to obtain a second layer of mesh cloth board; The second layer of mesh cloth plate is roll-formed by a forming pair of rollers to obtain a second UHPC structural plate, wherein the thickness of the second UHPC structural plate is 10-20 mm; The second UHPC structural panel moves forward along the conveyor belt to finally obtain a UHPC structural panel, wherein the UHPC structural panel includes n layers of mesh cloth.

7. The method for preparing a low-viscosity UHPC decorative board according to claim 6, characterized in that: The UHPC decorative panels include UHPC embedded component decorative panels and UHPC non-embedded component decorative panels. The UHPC decorative panel manufacturing method also includes: The surface material of the UHPC decorative board is measured and quantitatively released into the surface mixer; The surface layer template is coated with a release agent; When manufacturing the UHPC embedded component decorative board, the UHPC structural board is laid on the surface layer in two layers, and embedded components are placed between the two layers of the UHPC structural board to obtain the UHPC embedded component decorative board.

8. The method for preparing a low-viscosity UHPC decorative board according to claim 6, characterized in that: The method for manufacturing the structural layer is as follows: Step 1: Mix and stir white cement, special white silica powder, micro beads and textured quartz sand according to proportion to obtain a first mixed powder; Step 2: adding water, high-efficiency water reducing agent and defoaming agent into the first mixed powder according to proportion, stirring to obtain a first mixed slurry; Step 3: adding organic fiber to the first mixed slurry according to a proportion, stirring, and obtaining a second mixed slurry; Step 4: introducing the second mixed slurry into a molding machine, laying a mesh cloth, molding, and obtaining a structural layer.

9. The method for preparing a low-viscosity UHPC decorative board according to claim 7, characterized in that: The surface layer production method is as follows: Step 1: Mix and stir white cement, special white silica powder, micro beads, textured quartz sand and iron oxide color powder according to the proportion to obtain a second mixed powder; Step 2: adding water, acrylic emulsion, high-efficiency water reducing agent and defoaming agent into the second mixed powder according to proportion, stirring to obtain a third mixed slurry; Step 3: Add organic fiber to the third mixed slurry, stir evenly, and then add coarse aggregate and stir to obtain a fourth mixed slurry.